Simultaneous operations on abdominal aorta and biliary tract - A. S. Ivandaev; A. M. Kuznetsov; M. I. Vasilchenko («REMEDIUM GROUP» Ltd., 2022)
In this study we present a clinical case of simultaneous surgical treatment of a patient with an abdominal aorta aneurysm and cholelithiasis. Such a combination of diseases is rather common, but few centres have experience in performing simultaneous operations. In the literature, one can usually find observations or descriptions of small series of operations. The potential risk of infection of a synthetic prosthesis due to contamination of the prosthesis during cholecystectomy is one of the most significant constraining factors for performing simultaneous operations. Review of the available literature showed that most of the authors who promoted the staged treatment of this group of patients adhered to this position. On the other hand, dividing the treatment of two diseases into stages may be associated with specific complications of unoperated pathology. For instance, some authors described cases of aortic aneurysm rupture after cholecystectomy. On the other hand, there are publications that indicate the association between exacerbation of gallstone disease and resection of the aortic aneurysm. Contradicting outcomes and different points of view on potential risks associated with simultaneous and staged treatment approaches for this group of patients require analysis and determination of the optimal surgical technique to minimize the risks of infectious complications, aortic aneurysm rupture and exacerbation of cholelithiasis. Based on the presented observation and the other authors' review of the outcomes, we concluded that the simultaneous operations can be performed without risk. The compliance with a stage-by-stage approach to the operation which will minimize the risks of infection of the prosthesis is the main condition for the safe performance of such operations.